1998
DOI: 10.1590/s0036-36341998000200011
|View full text |Cite
|
Sign up to set email alerts
|

The role of vitamin A in reducing child mortality and morbidity and improving growth

Abstract: ARTÍCULO DE REVISIÓN The role of vitamin A in reducing child mortalityRamakrishnan U, Martorell R.The role of vitamin A in reducing child mortality and morbidity and improving growth. Salud Publica Mex 1998;40:189-198. AbstractThis is an update of knowledge on the role of the vitamin A status in determining child mortality, morbidity and growth. Recent information confirms the earlier conclusion of Beaton et al. that a 23% reduction in young child mortality results following improvements in the vitamin A statu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
1
4

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 69 publications
1
10
1
4
Order By: Relevance
“…The effects are greater in stunted children and in children with low serum zinc concentrations (3). The results of iron supplementation studies indicate positive effects in anemic children but not in nonanemic children (4)(5)(6)(7); there appear to be few or no effects of vitamin A on growth (8)(9)(10), except in children with severe deficiency (11).…”
Section: Introductionmentioning
confidence: 99%
“…The effects are greater in stunted children and in children with low serum zinc concentrations (3). The results of iron supplementation studies indicate positive effects in anemic children but not in nonanemic children (4)(5)(6)(7); there appear to be few or no effects of vitamin A on growth (8)(9)(10), except in children with severe deficiency (11).…”
Section: Introductionmentioning
confidence: 99%
“…Micronutrient supplementation, including therapeutic and preventative supplementation with zinc and therapeutic supplementation with vitamin A, has also been found to have positive impacts on diarrheal disease and death (Beaton and others 1993;Black 1998;Ramakrishnan and Martorell 1998;Zinc Investigators' Collaborative Group 1999Grotto and others 2003).…”
mentioning
confidence: 99%
“…In humans, vitamin A deficiency is now recognized as a highly significant risk factor associated with increased mortality in children and pregnant women (2,3). Intervention studies in at-risk populations have clearly demonstrated that providing vitamin A to children, ranging from newborn to 5 years of age, decreases child mortality rates by an average of 23%, with a 50% reduction observed in some studies (4,5). Furthermore, vitamin A supplementation has reduced measles-related mortality and the severity of several infectious diseases, including measles, diarrhea, malaria, and HIV infection (6 -9).…”
mentioning
confidence: 99%